The Spaces and Places of Jewish Emancipation during the Vormärz - Meola, David A. (European journal of jewish studies, 2024)
During the revolutionary era, Jews in the new Grand Duchy of Baden were given hope that full citizenship and integration would eventually be achieved. However, not every location or space in the Grand Duchy was inclusive, as Jews were excluded from most areas in civil society and the state. The Rhein-Neckar region (including the cities of Mannheim and Heidelberg), however, proved to be a location where close contact between Jews and Christians was not only more regular, but an important facet of the developing liberal society—whether that was in the newspapers, the classroom, or bourgeois associations. These so-called ‘fraternal spaces’ shaped the individuals and were shaped by those individuals who came through them. In the case of the Rhein-Neckar region, this led to Jewish-Christian relationships that had an indelible impact on the blossoming liberal movement of the Vormärz as well as the lead-up to the 1848 revolutions.